Effect of laser heat treatment on microstructure of magnesium alloy - Ong, Yu Qi (2014)
Use of Magnesium alloys in biomedical applications has been increasing throughout the years and much research and development had been done to improve the corrosion properties of the alloys. One of the more promising way is to make use of laser heat treatment to change the microstructure of the magnesium alloy in a bid to improve its corrosion resistance.